2003
DOI: 10.1097/01.brs.0000051920.45671.88
|View full text |Cite
|
Sign up to set email alerts
|

Intradiscal Pressure Study of Percutaneous Disc Decompression With Nucleoplasty in Human Cadavers

Abstract: Pressure reduction through nucleoplasty is highly dependent on the degree of spine degeneration. Nucleoplasty markedly reduced intradiscal pressure in nondegenerative discs, but had a negligible effect on highly degenerative discs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
84
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 19 publications
1
84
0
Order By: Relevance
“…In contrast, IDP change in healthy individuals moving from a flexion to an extension posture followed a quadratic relationship. Nucleus pressure was raised corresponding to increase in volume by the injection of fluid (Andersson and Schultz 1979;Ranu 1993) and fell when the volume was decreased by either surgical excision (Brinckmann and Grootenboer 1991) or nucleoplasty (Chen et al 2003). There was a reduction in the hydrostatic pressure in the functional nucleus of discs that were subjected to rigorous creep loading; 1-2 kN maintained for 2-3 h (Adams et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, IDP change in healthy individuals moving from a flexion to an extension posture followed a quadratic relationship. Nucleus pressure was raised corresponding to increase in volume by the injection of fluid (Andersson and Schultz 1979;Ranu 1993) and fell when the volume was decreased by either surgical excision (Brinckmann and Grootenboer 1991) or nucleoplasty (Chen et al 2003). There was a reduction in the hydrostatic pressure in the functional nucleus of discs that were subjected to rigorous creep loading; 1-2 kN maintained for 2-3 h (Adams et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In the older, degenerative disk cadavers, the change in intradiscal pressure after nucleoplasty was very small. There was an inverse correlation between the degree of disk degeneration and the change of intradiscal pressure [10].…”
Section: Introductionmentioning
confidence: 84%
“…The effect of decreasing intradiscal pressure by nucleoplasty is still controversial. Chen et al demonstrated a noticeable reduction in disc pressure after using nucleoplasty in human cadavers, but there is still no irrefutable evidence in vivo [27]. A possible explanation of coblation effect may be the thermal effect of nucleoplasty.…”
Section: Discussionmentioning
confidence: 99%